(untitled) (Academicia Globe: Inderscience Research, 2022)
The article presents data on injuries of the genital organs of women and their consequences. The work was carried out on the basis of the gynecological department of the clinic of the Samarkand State Medical University. The survey showed that surgical treatment was necessary in 24% of cases.